EVALUASI PROGRAM LITERASI PENDIDIKAN DI SMK KESEHATAN TRI BHAKTI AT-TAQWA UNTUK MENYONGSONG REVOLUSI INDUSTRI 4.0. - Zainal Ramadhan (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is aimed to evaluate educational literacy programs in high school health Tri Bhakti At-Taqwa. This type of research is qualitative descrptive. The main sourceof this research is the principal, teachers and students by using collecting data through interview, observation and documentation. The legitimate of the research datais using source and technique triangulation. The data is interatively analized which content of data collection, data reduction, serving data, concluding and verification. The writer caninfer that 1) literacy Program in high school health Tri Bhakti At-Taqwa play sarolein motivating students to love reading and writing, 2) the school obstac lesto improve reading and writing interest using literation activityare discipline, student’shabit, student’s interest,and the method applied by the teacher,and, 3) the school effortto improve the students reading and writing interest through literation activityis that theschool always gives literation activity socialization and motivation regarding the impotance of reading and writing.